Aplicação da inteligência artificial para suporte ao processo decisório e estratégico - Farias, Guilherme Ehlers (2025)
The integration of Artificial Intelligence (AI) in strategic decisions has reshaped organizational dynamics in various sectors, automating analyses and enabling more agile and informed decisions. This study explores the application of AI in strategic decisions, focusing on its implementation in the governance of the Investment Fund of Guarantee Fund for Length of Service (FI-FGTS). The research is justified by AI's ability to overcome human limitations, such as time constraints and biases, as well as the ethical and governance challenges that arise from its use. The proposed methodology involves a literature review and a case study in the governance of a public bank, through the analysis of strategic propositions. The findings indicated that the risk agent performed satisfactorily in part of the analyses, while the compliance agent showed consistent performance, but with deviations from the expected standard. The results are expected to show that the use of AI promotes more structured decisions and, consequently, strengthens governance.